2021
DOI: 10.1590/1413-81232021263.42372020
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerabilidade social e incidência de COVID-19 em uma metrópole brasileira

Abstract: Resumo A vulnerabilidade é um fator chave no enfrentamento da COVID-19 tendo em vista que pode influenciar no agravamento da doença. Desse modo, ela deve ser considerada no controle da COVID-19, prevenção e promoção da saúde. O objetivo deste artigo é analisar a distribuição espacial da incidência de casos de COVID-19 em uma metrópole brasileira e sua associação com indicadores de vulnerabilidade social. Estudo ecológico. Foi utilizada a análise de varredura espacial (scan) para identificar aglomerados de COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 13 publications
2
19
0
19
Order By: Relevance
“…Fato observado no Brasil a nível municipal, estadual e regional (DEMENECH, 2020;SANHUEZA-SANZANA, 2020;FIGUEIREDO, 2020;CESTARI, 2021;CHPC, 2020). Paraná (28,3), Rio Grande do Sul (29,8) e Santa Catarina (31).…”
Section: Resultsunclassified
“…Fato observado no Brasil a nível municipal, estadual e regional (DEMENECH, 2020;SANHUEZA-SANZANA, 2020;FIGUEIREDO, 2020;CESTARI, 2021;CHPC, 2020). Paraná (28,3), Rio Grande do Sul (29,8) e Santa Catarina (31).…”
Section: Resultsunclassified
“…The adoption of measures such as avoiding continuous access to news about the COVID-19 pandemic, for example, is an effective self-care measure for both adults and children. One should focus on attitudes that promote our well-being, such as the practice of physical activity and stretching 21 .…”
Section: /15mentioning
confidence: 99%
“…Generally, the highest cases are related to larger populations, with residents in densely populated places and with lower income levels being at greater risk of infection by Covid-19 (Quinino, 2021). Another study concluded that the highest incidence of Covid-19 occurs in territories with an urban majority and high population density (Cestari et al, 2021). In Argentina, the highest mortality rates occur in regions with a higher population density and a higher percentage of the elderly population (Leveau, 2021).…”
Section: Echoes Of Urban Densification In Speeches About Fighting Aga...mentioning
confidence: 99%